The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1016/j.resuscitation.2006.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Quality of out-of-hospital cardiopulmonary resuscitation with real time automated feedback: A prospective interventional study

Abstract: ClinicalTrials.gov (NCT00138996), http://www.clinicaltrials.gov/.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
310
6
20

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 451 publications
(351 citation statements)
references
References 30 publications
15
310
6
20
Order By: Relevance
“…A p-value < 0.05 was defined as statistically significant. The sample size calculation was based on the comparison of the primary end point in the three groups; we did not perform earlier studies that would have been useful as a basis for a sample size calculation; therefore, based on previous studies, [36][37][38] we wanted to adequately detect a mean paired difference of 0.7 times the standard deviation. Based on an alpha = 0.05 and a power of 80%, a sample size of 37 study participants per group was needed.…”
Section: Resultsmentioning
confidence: 99%
“…A p-value < 0.05 was defined as statistically significant. The sample size calculation was based on the comparison of the primary end point in the three groups; we did not perform earlier studies that would have been useful as a basis for a sample size calculation; therefore, based on previous studies, [36][37][38] we wanted to adequately detect a mean paired difference of 0.7 times the standard deviation. Based on an alpha = 0.05 and a power of 80%, a sample size of 37 study participants per group was needed.…”
Section: Resultsmentioning
confidence: 99%
“…It is becoming increasingly recognised that survival is affected not only by whether CPR is performed, but also by its quality. Recent evidence has confirmed the importance of chest compression depth [4][5], rate [6], releasing pressure between compressions [7], minimising interruptions in CPR [8], avoiding pauses prior to defibrillation [9] and not hyperventilating the patient [10] to ensure the optimal effectiveness of resuscitation. Despite the knowledge that the quality of CPR is of critical importance to outcomes, studies consistently demonstrate that the quality of CPR performed in real life by both laypersons [11] and healthcare providers [12][13][14] is frequently sub-optimal.…”
mentioning
confidence: 99%
“…The recommended chest compression depth is now at least 2 inches on the basis of studies that demonstrated improved defibrillation success and short-term outcomes with increased compression depth, and the recommended compression rate is at least 100 per minute. 16,24,25 In addition to guideline changes, public education and CPR training are paramount because laypersons trained in CPR are significantly more likely to perform CPR. 26 …”
Section: Bystander Cprmentioning
confidence: 99%
“…Two alternate studies examining real-time feedback, one of which used the addition of weekly debriefing, both improved the quality of CPR and demonstrated better short-term outcomes. 25,41 Laypersons not trained in CPR may be able to provide effective CPR with assistance from emergency medical system (EMS) dispatchers. Dispatch-assisted CPR has been demonstrated to be safe and to increase the rates of bystander CPR and may improve survival from cardiac arrest.…”
Section: Airway and Breathingmentioning
confidence: 99%